Is Academic Feminism Dead? : Theory in Practice. - The Social Justice Group (NYU Press, 2000)
What role does theory play in academia today? How can feminist theory be made more relevant to the very real struggles undertaken by women of all professions, races, and sexual orientation? How can it be directed into more effective social activism, and how is theory itself a form of practice?. Feminist theory and political activism need not--indeed cannot--be distinct and alienated from one another. To reconcile the gulf between word and deed, scholar-activists from a broad range of disciplines have come together here to explore the ways in which practice and theory intersect and interact. The.